Information technology for management : new ideas and real solutions : 14th Conference, AITM 2016, and 11th Conference, ISM 2016, held as part of FedCSIS, Gdansk, Poland, September 11-14, 2016, Revised selected papers /: new ideas and real solutions : 14th Conference, AITM 2016, and 11th Conference, ISM 2016, held as part of FedCSIS, Gdansk, Poland, September 11-14, 2016, Revised selected papers. (2017) - Unknown
No abstract available